O papel do editor no processo de edição do Manual do Professor - Nogueira, Paola de Oliveira (2018)
This work has an exploratory character and seeks to understand the role of the editor in the process of editing the specific version of textbooks produced for teachers, known as the Teacher's Guide. In this sense, its main objectives were to map the stages and the actors engaged in the process of editing the Teacher's Guide currently developed in Brazilian publishing houses and to analyze the role played by editors in this process, observing the profile of these professionals, the functions they perform in editing the Teacher’s Guide and the internal and external factors that influence this work. The theoretical reference framework is located in the area of History of Education and, particularly, in the area of History of Curriculum and Textbooks. The methodological procedures were the application of a questionnaire and interviews with editors of the two largest Brazilian textbook publishing houses. The interpretation of the data collected in the field research was based on the theoretical framework presented above and suggests that the main functions performed by editors in the editing process of the Teacher's Guide are related to coordinating activities of other professionals, editing and organizing the original text and writing or rewriting this material. In addition, the analysis of the data collected indicates that editors recognize the Teacher's Guide as an important material for training teachers, presenting the prescribed curriculum, mastering contents and planning classes, although they do not have objective information on how teachers use this material. In this way, by analyzing the practices developed by editors in the editing process of the Teacher's Guide, the work contributes to broadening the understanding about the set of practices that define the curricular system and that, in this sense, directly interfere with the current pedagogical practice